The prevalence of depression/anxiety among patients with rheumatoid arthritis and its relationship with quality of life - Ćeranić Jelena; Glišić Branislava; Petronijević Milan; Kisić-Tepavčević Darija; Ristić Gorica (Vojnosanitetski Pregled, 2022)
Background/Aim. Rheumatoid arthritis (RA) is accompanied by numerous comorbidities, among which depression and anxiety (D/A) occupy a significant place. The aim of the study was to determine the prevalence of D/A in RA patients and the relationship with their quality of life (QoL). Methods. The study included RA patients treated at the Rheumatology Clinic of the Military Medical Academy in Belgrade, Serbia in the period from May to November 2016. Disease activity was assessed by the Disease Activity Score 28-SE (DAS28-SE). D/A was determined using the Hospital Anxiety and Depression Scale (HADS) questionnaire and European Quality of Life 5 Dimensions 3 Level Version (EQ-5D-3L) questionnaire Question 5. Three questionnaires were used to assess QoL: the general RAND 36-item Health Survey 1.0 (RAND36), the specific Rheumatoid Arthritis Quality of Life Questionnaire (RAQoL) and EQ-5D-3L. Results. Based on the HADS questionnaire, the prevalence of depression was 52% with the average HADS score value of 7.6 ± 3.2, while the prevalence of anxiety was 32% with the mean HADS score value of 5.8 ± 3.8. Question 5 of the EQ-5D questionnaire showed that the prevalence of D/A was 77.4%, of which 71.7% of patients had moderate D/A, while 5.7% of patients had severe D/A. Impairment in all the domains of QoL was found in tested patients, as assessed by all three questionnaires. The RAQoL questionnaire showed moderate QoL impairment, with a score value of 15.5 ± 7.9. The EQ-VAS score value was 58.6 ± 16.0, while the EQ-5D index was 0.6 ± 0.3. Univariate linear regression produced a statistically significant negative predictive value of QoL for the presence of D/A. Multivariate linear regression showed a statistically significant independent negative predictive value of QoL, as assessed by the RAQoL questionnaire (p = 0.010) and the mental QoL component of the RAND 36 questionnaire (p = 0.030) for the degree of depression. Conclusion. In RA patients, there is a significant prevalence of D/A as well as impairment of QoL in all domains. The tests performed have shown that QoL has a statistically significant negative predictive value for the presence of D/A.